Mathematical Engagement When Solving Mathematical Problem With Brawijaya Temple Context Based on Mathematical Ability Level - Alfaoundra, Valerient Trisna; Hayuhantika, Diesty; Santoso, Achmad Budi (Universitas Muhammadiyah Mataram, 2020)
This research to describe the mathematical engagement of seventh grade junior high school students in problems solving with the theme of Brawijaya Temple with high, medium, and low levels of mathematical ability. This type of research is qualitative research using an exploratory approach. The students used were 6 grade VII students of Junior High School 1 Karangrejo who were students working on problem solving and interviewing. The results showed: (1) mathematical engagement of highly skilled students in problems solving with the theme of Brawijaya Temple, namely students having the engagement of “get the job”, (2) mathematical engagement of students with moderate abilities in problems solving with the theme of Brawijaya Temple, namely students having engagement is “I am really into this”, (3) Mathematical engagement of students with low abilities in problems solving with the theme of Brawijaya Temple is that students have “pseudo-engagement”.